Digital Transformation of Academic Administration Services: Isomorphism Analysis at Madako University Tolitoli - Muhammad Iqbal; Nursifa; Masrin Gafar; Henra Rasa Putra; Eka De Patmonsela Liow (Perkembangan Kajian Sosial, 2026)
This study analyzes the public administration transformation process at Tolitoli Madako University within the framework of institutional theory, specifically the concept of isomorphism (coercive, mimetic, normative). Using a descriptive qualitative approach that incorporates participant observation, in-depth interviews, and documentary studies, the study examines how regulatory pressures, imitation of institutional practices, and professional demands shape academic administrative policies and practices amid digital disruption. The results indicate the dominance of coercive isomorphism, which drives the adoption of SOPs and formal digital systems, accompanied by mimetic isomorphism that results in the partial adoption of modern practices, and normative isomorphism that is just beginning to form but is not yet supported by a strong human resource capacity and evaluation mechanisms. The findings reveal a gap between formal digital design and daily operational practices, such as reliance on physical documents, manual flows, and limited digital literacy/infrastructure, resulting in transformation tending to be procedural or symbolic. Recommended strategies include simplifying and integrating SOPs into centralized digital systems, strengthening human resource training and performance indicators, and a selective and contextual mimetic adaptation approach to ensure substantive and sustainable change.